Multivariate analysis of the impact of weather and air pollution on emergency department visits for night-time headaches among children: retrospective, clinical observational study - Kandai Nozu; Hiroshi Yamaguchi; Hiroki Takeda; Kazumoto Iijima; Hiroaki Nagase; Ichiro Morioka; Shinya Ishiko; Takeshi Ninchoji; China Nagano; Ai Unzaki; Kazuto Ishibashi; Akihito Ishida (BMJ Open, 2021)
Objectives To examine the association between the number of visits to the emergency department (ED) by children for night-time headaches and exposure to multifaceted factors, such as meteorological conditions and air pollution.Design We conducted a clinical observational time-series analysis study.Setting We reviewed consecutive patients younger than 16 years of age at the primary ED centre in Kobe city, Japan, during the night shift (19:30–7:00 hours) between 1 January 2011 and 31 December 2019.Participants In total, 265 191 children visited the ED; 822 presented with headache during the study period.Primary outcome measures We investigated the effects of meteorological factors and air pollutants by multivariate analysis of Poisson regression estimates. A subanalysis included the relationship between the number of patients with night-time headaches and the above factors by sex. Furthermore, the effect of typhoon landing on patient visits for headache was also analysed. Headache was not classified because examinations were performed by general paediatricians (non-specialists).Results The number of patients with night-time headaches displayed distinct seasonal changes, with peaks during the summer. Multivariate analysis of Poisson regression estimates revealed a significant positive relationship between the number of patients for headache and mean temperature. Subanalysis by sex indicated a positive relationship between the number of patients with headache and mean temperature in both sexes; however, it was significant only for females. No relationship was found between the number of patients with headache and air pollution. There was no change in the number of patients for night-time headaches 3 days before and after typhoon landing.Conclusions High temperature is the main factor for visiting ED for night-time headaches among children in Kobe city. Our results suggest that preventive measures against night-time headaches may be possible by reducing time spent outside during summer.